Pendidikan Islam Di Andalusia: Cahaya Ilmu Di Semenanjung Iberia - Nazla Desyulita; Baiq Uswatun Hasanah; Abdul Halim; Faelasup (CV. ITTC INDONESIA, 2024)
Muslims were the first to become the spearheads of progress over the ignorance that previously was still ongoing, as well as the oppression of previous rulers due to tyrannical leadership. Several factors created opportunities for Muslims to prepare to raise the flag of monotheism and the important role of Muslim rulers and religious leaders was very influential in making Andalusia reach a glorious peak that advanced science and civilization. This article will reveal historical facts about Andalusian education during the heyday of Islam and the figures who played an important role in building scientific progress there. The discussion that will be carried out in this article concerns the history of the arrival of Islam in Andalusia, and the education that emerged, developed and is influential to this day. This research was carried out by rewriting, reducing, clarifying and presenting data based on written data sources. The history and literature on Islamic heritage that covers Andalusia is a symbol of the golden age of Islam there at that time. In the Islamic education sector, currently many educational places and forums are being built. This sector is divided into 3 positions, namely primary, higher and library education. They studied a lot of music, language, science, philosophy, religion. The support of the authorities also included the role of progress in education at that time.